The Implementation of ADDIE Model in Developing Career Guidance Program in Senior High School - Indri Astuti (JETL (Journal of Education, Teaching and Learning), 2019)
The research aims to reveal the factual design and conceptual design of the preparation of career guidance programs at Pontianak 3 State Senior High School. Sixty twelve grade science students and two guidance and counseling teachers were also the subjects of the survey. Quantitative data were obtained using questionnaires as main data and interviews as additional data. The results of data processing show that most of the assessment needs have been carried out in a high category. However, the response of the guidance and counseling (BK) teacher stated that there were still weaknesses in the factual model of the preparation of the BK program in the field of career guidance including the principal, homeroom teacher and subject teacher had not been involved in the preparation of the BK program. So this finding is the basis for the preparation of the conceptual design of career guidance programs, that the involvement of principals, homerooms and subject teachers has been apparent in the process of developing a career guidance program.